Will - Will Smith, with Mark Manson (New York Penguin Press, an imprint of Penguin Random House LLC, 2021)
A product of a profound journey of self-knowledge, and a reckoning with all that your will can get you and all that it can leave behind, in this memoir, one of the most dynamic and globally recognized entertainment forces of our time opens up fully about his life.
Keywords: Smith, Will, 1968-